FACTORS AFFECTING THE VALUE OF ENTITIES ON THE INDONESIA STOCK EXCHANGE - Nathasya Elizabeth Joy; Riki Sanjaya (Kesatuan Press, 2022)
The objective of this research is to obtain empirical evidence about the influence of liquidity, leverage, dividend policy, firm size, profitability, institutional ownership, and managerial ownership as independent variables to firm value as dependent variable in Indonesia non-financial companies. The research used companies listed in non-financial sectors in Indonesia Stock Exchange on 2018-2020. There are 103 companies meet the criteria by using purposive sampling method. The research uses multiple regression method for data analysis. The result shows that leverage and profitability have influence to firm value, while other independent variables such as liquidity, dividend policy, firm size, institutional ownership and managerial ownership have no influence towards firm value in the company.